Judicial Pardon for Minor Offenses from the Perspective of Fiqh Jinayah: Pemaafan Hakim (Judicial Pardon) Terhadap Tindak Pidana Ringan Dalam Perspektif Fiqh Jinayah - Rahman, Abd; Haq, Islamul; Muliyati, Muliyati; Anwar, Alfiansyah (Universitas Islam Negeri Alauddin Makassar, 2025)
This research aims to examine the concept of forgiveness in minor crimes from the perspective of fiqh jinayah and analyze the gap between the principle of judicial forgiveness in Indonesian positive law and Islamic legal values. Judicial pardons in the Indonesian legal system are special powers given to judges to mitigate or exempt perpetrators from criminal sanctions, especially for minor crimes that do not have a significant impact on society. This concept is a form of judicial discretion in which judges can refrain from imposing sentences even if the defendant is proven guilty. This research uses a normative method with a conceptual and legislative approach, through an analysis of Law Number 1 of 2023 concerning the Criminal Code (KUHP) and jinyayah fiqh literature. The results of the study show that judicial pardon for minor crimes has similar principles to forgiveness in fiqh jinayah, such as consideration of the benefit of the community (maslahah), protection of victims' rights, and the application of proportionate punishment so as not to cause excessive deterrent effects. These findings indicate that judicial pardons can be integrated as an alternative mechanism for resolving minor criminal cases while upholding the principles of restorative justice and a balance between the rights of victims and the rehabilitation of perpetrators. The integration of the values of fiqh jinayah into the concept of judicial forgiveness has the potential to enrich Indonesia's positive legal practice in realizing a more humanistic and beneficial criminal justice system.